Strategic Awareness and Digitalization in the Supply Chains of the Agricultural and Food Industry - Ulechla, Gergely; Szegedi, Zoltán (Advances in Social Sciences Research Journal, 2022)
The purpose of our research is to study the factors characterizing strategic awareness and digitalization in the supply chains of the agricultural and food industry in the Central and Eastern European region. In the article, the authors assess the conditions and preparedness of corporate strategy, structural changes, and strategic awareness when aiming for digital transformation as a key objective that provides a competitive edge. The article is founded on a questionnaire that was developed specifically for this research as the basis of Gergely Ulechla’s PhD dissertation. The results reveal the most important motivating factors and differences in the diverse approaches to the process of strategy formulation.